1999
DOI: 10.1021/la9804177
|View full text |Cite
|
Sign up to set email alerts
|

Mixed Micelles Containing Alkylglycosides:  Effect of the Chain Length and the Polar Head Group

Abstract: The mixing behavior of binary mixtures of the pure alkylglycosides:  β-decylglucoside (β-C10G), β-dodecylglucoside (β-C12G), β-decylmaltoside (β-C10M), and dodecylmaltoside (C12M) in combination with different common surfactants has been studied. First, the effect of the nonionic polar headgroup and chain length of the glycosidic surfactants in the mixed micellization with sodium dodecyl sulfate (SDS) was investigated. Further on, to analyze the effect of the ionic headgroup on the micellization of the glycosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
52
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(56 citation statements)
references
References 42 publications
3
52
1
Order By: Relevance
“…E-mail: pernilla.liljekvist@ surfchem.kth.se. has a small positive charge character, which is consistent with other studies (2)(3)(4)(5)(6)(7). This was also supported by a slightly negative β CMC parameter obtained for the surfactant mixture C 10 M-C 10 EO 8 , indicating a small net attractive interaction between the two nonionic surfactants.…”
Section: Introductionsupporting
confidence: 91%
“…E-mail: pernilla.liljekvist@ surfchem.kth.se. has a small positive charge character, which is consistent with other studies (2)(3)(4)(5)(6)(7). This was also supported by a slightly negative β CMC parameter obtained for the surfactant mixture C 10 M-C 10 EO 8 , indicating a small net attractive interaction between the two nonionic surfactants.…”
Section: Introductionsupporting
confidence: 91%
“…Surface tension of industrial grade APG and linear alkyl benzene sulfonate and fatty alcohol ethoxylates, respectively, have also been investigated with respect to their technical use (9). A comprehensive study of the mixed micelle interaction between different APGs and between an APG and ionic or nonionic (ethoxylated) surfactants have also been conducted (10).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, this problem has received considerable attention in recent years [8][9][10][11][12][13][14][15][16][17][18][19]. One of the more interesting aspects in this kind of studies is that, as all ionic surfactants have the same head group, the differences observed can be attributed to the length of their hydrocarbon chain.…”
Section: Introductionmentioning
confidence: 99%